2016
DOI: 10.1071/an13442
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive statistics and the pattern of horse racing in New Zealand. 1. Thoroughbred racing

Abstract: The aim of the present study was to describe the pattern of flat and jump races and starts, including temporal trends, in Thoroughbred racing in New Zealand. Data on all race starts between 1 August 2005 and 31 July 2011 were supplied by New Zealand Thoroughbred Racing. Descriptive statistics were used to describe the data at both race and start level, stratified by flat and jumps races. In total, 96% of races run were flat races and most races and starts occurred in the Northern region. There was an even dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Despite only a small difference in number of racetracks between the North and South Islands, there is a significantly greater concentration of Thoroughbred racing in the North Island of New Zealand, approximately 75% of all races and starters [15], which was reflected in the number of starters for the respective tracks in the North Island. Horses in training within the northern region of the North Island were also more likely to race, which may in part be because of clustering of the more successful trainers in this region [16,17].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Despite only a small difference in number of racetracks between the North and South Islands, there is a significantly greater concentration of Thoroughbred racing in the North Island of New Zealand, approximately 75% of all races and starters [15], which was reflected in the number of starters for the respective tracks in the North Island. Horses in training within the northern region of the North Island were also more likely to race, which may in part be because of clustering of the more successful trainers in this region [16,17].…”
Section: Discussionmentioning
confidence: 97%
“…Starters and number of race meetings were also stratified according to regional or premier tracks within the different racing regions, with more race meetings, at a higher frequency, at premier tracks. These premier tracks and meetings also attract horses from a greater catchment area [15,18].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The rationalisation of the New Zealand Thoroughbred industry has seen a reduction in the number of mares bred for the domestic market, while the export-focused sector has seen little change in numbers (Bolwell et al 2014). The reduced number of active broodmares and sires was associated with an increase in efficiency and less supply-chain wastage.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the majority of the top 10 nations involved in Thoroughbred racing and breeding, the New Zealand industry is heavily reliant on the export market, rather than production of horses as domestic racing product (Fennessy 2010). Previous examination of the production process has identified that approximately 40% of the annual foal crop are exported (Bolwell et al 2014), and that the industry could be considered to operate as two sectors or tiers -one sector focused largely on the export market and another group of smaller breeders (fewer mares per breeder) focusing on the domestic market . The export market was characterised by the use of shuttle sires (stallions breeding in the Northern and Southern Hemispheres in one calendar year) and expensive sires (>$10,000 service fee), while the domestic market was serviced by the low-cost (<$5,000 service fee) and to a lesser extent, medium-cost sires ($5,000 -$10,000 service fee).…”
Section: Introductionmentioning
confidence: 99%